Carbon-coated molybdenum nitride nanoparticle embedded lead-nitrogen co-doped carbon catalyst as well as preparation method and application thereof
By coating molybdenum nitride nanoparticles with lead-nitrogen co-doped carbon catalyst, the synergistic effect of Mo and Pb is used to solve the problem of competition in hydrogen precipitation reactions in electrochemical synthesis ammonia, improving ammonia yield and Faraday efficiency, realizing Low-cost and efficient nitrogen reduction reaction.
Patent Information
- Application Number
- CN202411401005.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
AI Technical Summary
The existing electrochemical ammonia synthesis technology is subject to thermodynamic and kinetic challenges, resulting in low ammonia yield and Faraday efficiency, and serious competition in hydrogen precipitation reactions of transition metal catalysts, reducing selectivity.
Carbon-coated molybdenum nitride nanoparticles embedded in lead-nitrogen co-doped carbon catalyst, through the synergy between transition metal Mo as the main nitrogen reduction active site and p-region metal Pb, the nitrogen reduction activity and selectivity of the catalyst are improved, and the nitrogen reduction activity and selectivity of the catalyst are inhibited. Hydrogen precipitation reaction.
The ammonia yield and Faraday efficiency of electrochemical synthesis ammonia are significantly improved, the stability and selectivity of the catalyst are enhanced, and the preparation cost is reduced.
Smart Images

Figure CN119287428A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical ammonia synthesis, and in particular relates to a carbon-coated molybdenum nitride nanoparticle embedded with lead and nitrogen co-doped carbon catalyst, and a preparation method and application thereof. Background Art
[0002] Ammonia (NH3) is one of the important chemical products in modern society and has important applications in agriculture and industry. At present, the industrial production method of NH3 is mainly the Haber-Bosch process (HBP) with harsh reaction conditions (high temperature (400-600°C), high pressure (20-40MPa)), and the energy consumption is as high as 1%-2% of the total global energy consumption. In addition, every kilogram of NH3 produced will produce 2.16kg of greenhouse gases (CO2), accounting for 1.5% of the total global emissions. Therefore, it is urgent to develop a low-energy and environmentally friendly method for synthesizing ammonia.
[0003] With the rapid development of new energy and the continuous reduction of the price of renewable energy electricity, electrochemical synthesis of ammonia (ENRR) directly from nitrogen and water, driven by renewable energy, is one of the most promising routes for synthesizing ammonia. However, ENRR is subject to both thermodynamic and kinetic challenges, resulting in low ammonia yield and Faraday efficiency. Therefore, it is urgent to develop efficient electrocatalysts to improve the activity and selectivity of ENRR. At present, transition metal-based catalysts have received much attention due to their superior ENRR activity. However, due to the strong coupling between the d orbital of the transition metal and the s orbital of hydrogen, the hydrogen evolution reaction (HER) competes severely, which greatly reduces the selectivity of the ENRR of the transition metal catalyst and reduces the Faraday efficiency.
[0004] To solve this problem, the present invention proposes a preparation method and application of a novel catalyst. A transition metal (Mo) with high ENRR activity is used as the main active site of the catalyst, and the ENRR selectivity is improved by introducing a p-block metal (Pb) that inhibits the hydrogen evolution reaction, constructing a transition metal and p-block metal composite catalyst, and utilizing the synergistic effect between Mo and Pb metals to improve the activity and selectivity of the catalyst. Summary of the invention
[0005] In order to solve the above problems existing in the prior art, the present invention provides a carbon-coated molybdenum nitride nanoparticle embedded lead-nitrogen co-doped carbon catalyst and its preparation method and application, aiming to improve the ENRR activity and selectivity of the catalyst. The transition metal Mo in the catalyst is used as the main nitrogen reduction active site, and has excellent nitrogen reduction activity due to its good adsorption of nitrogen. At the same time, the p-zone metal Pb with extremely poor competitive hydrogen evolution performance is introduced to reduce the HER activity of the catalyst and thus improve the nitrogen reduction selectivity of the catalyst. Through the synergistic effect of Mo and Pb, the ENRR catalytic activity and selectivity of the catalyst are effectively improved.
[0006] The invention relates to a preparation method of a carbon-coated molybdenum nitride nanoparticle embedded in a lead-nitrogen co-doped carbon catalyst. Zinc nitrate and metal salts are used, and 2-methylimidazole is used as a ligand to prepare a zeolite imidazolate metal organic framework material (ZIFs) through coordination self-assembly. Then, the transition metal molybdenum salt and p-region metal lead salt are adsorbed by the rich pore structure of ZIFs, and the carbon-coated molybdenum nitride nanoparticle embedded in the lead-nitrogen co-doped carbon catalyst is prepared through high-temperature pyrolysis and acid washing. At high temperature, molybdenum ions combine with nitrogen in ZIFs to generate carbon-coated molybdenum nitride nanoparticles. At the same time, the presence of Mo promotes the conversion of surrounding amorphous carbon into highly crystalline graphite carbon. The unique structure stabilizes molybdenum nitride on the surface of lead-nitrogen co-doped carbon, which is beneficial to improving the stability of molybdenum nitride in an electrolyte.
[0007] To achieve this purpose, the present invention adopts the following technical scheme: a carbon-coated molybdenum nitride nanoparticle is embedded in a lead-nitrogen co-doped carbon catalyst, the catalyst presents a dodecahedral morphology, with a diameter of about 137 to 180 nm, wherein the molybdenum nitride nanoparticles are dispersed on the surface of the doped carbon, the Mo content is 0.8 to 2.5 wt.%, and the Pb content is 0.1 to 0.7 wt.%.
[0008] In a preferred embodiment of the present invention, the carbon-coated molybdenum nitride nanoparticles are molybdenum nitride coated with a graphite carbon layer, wherein the average particle size of the carbon-coated molybdenum nitride nanoparticles is 3 to 7 nm, and the thickness of the graphite carbon layer is 1 to 4 nm. The molybdenum nitride nanoparticles are coated with a highly graphitized carbon layer, so that they can be stably embedded in the surface of the lead-nitrogen co-doped carbon support. This unique structure can prevent the metal from dissolving during the electrocatalyst reaction, significantly improving the electrochemical stability. The carbon-coated molybdenum nitride nanoparticles are embedded in the lead-nitrogen co-doped carbon catalyst, and molybdenum can improve the ENRR activity of the catalyst, while lead can improve the ENRR selectivity of the catalyst.
[0009] The present invention also protects a method for preparing the carbon-coated molybdenum nitride nanoparticles embedded with lead-nitrogen co-doped carbon catalyst, comprising the following steps:
[0010] (1) Dissolving zinc nitrate hexahydrate and 2-methylimidazole in anhydrous methanol by stirring;
[0011] (2) pouring a methanol solution containing zinc nitrate hexahydrate into a methanol solution containing 2-methylimidazole, and keeping the temperature for a period of time to obtain a zeolite imidazolate metal organic framework material;
[0012] (3) adding a certain mass ratio of transition metal molybdenum salt and p-block metal lead salt to the solution of (2) above, stirring at room temperature, and then filtering, washing, and drying the solution to obtain a zeolite imidazolate metal organic framework material adsorbing molybdenum salt and lead salt;
[0013] (4) subjecting the precursor obtained in (3) to high temperature pyrolysis to obtain a black powder;
[0014] (5) The black powder obtained in the above (4) is dispersed in an acid solution, stirred at room temperature, filtered, washed, and dried to obtain a carbon-coated molybdenum nitride nanoparticle embedded with a lead-nitrogen co-doped carbon catalyst.
[0015] In a preferred embodiment of the present invention, in step (2), the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:4, and the mixture is kept in an oven at 40-70° C. for 6-8 hours.
[0016] In a preferred embodiment of the present invention, in step (3), the transition metal molybdenum salt is one or more of molybdenum chloride, sodium molybdate, and ammonium molybdate, the p-block metal lead salt is one or more of lead chloride, lead nitrate, and lead acetylacetonate, and the molar ratio of the transition metal molybdenum salt to the p-block metal lead salt is 1:4; stirring is carried out at room temperature for 10-12 hours.
[0017] In a preferred embodiment of the present invention, in step (4), the high temperature pyrolysis is carried out in an inert atmosphere, the insulation temperature is 800-1000°C, the insulation time is 2-3h, and the heating rate is 3-8°C min -1 ; The inert atmosphere is nitrogen or argon.
[0018] In a preferred embodiment of the present invention, in step (5), the acid solution is one or more of nitric acid and acetic acid, with a concentration of 0.5-2M; stirring is performed at room temperature for 4-6 hours. The purpose of pickling is to remove surface instability and surface impurities.
[0019] The present invention also protects the use of the carbon-coated molybdenum nitride nanoparticles embedded in the lead-nitrogen co-doped carbon catalyst in the electrochemical synthesis of ammonia.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] (1) The raw materials used in the carbon-coated molybdenum nitride nanoparticles embedded in the lead-nitrogen co-doped carbon catalyst are readily available and low-cost, and the method is controllable, which is conducive to reducing the preparation cost compared with precious metal-based catalysts;
[0022] (2) In order to solve the problem that nitrides are easy to decompose and have poor stability in the electrolyte, the present invention constructs a doped carbon catalyst embedded with molybdenum nitride nanoparticles by in-situ coating of a carbon layer. The presence of molybdenum will promote the conversion of the surrounding amorphous carbon into a highly crystalline graphite carbon layer, so that the carbon-coated molybdenum nitride nanoparticles are stably embedded in the surface of the lead-nitrogen co-doped carbon, effectively improving the stability of the catalyst in the electrolyte;
[0023] (3) In the present invention, transition metal Mo is used as the main active site of ENRR. The empty d orbital of transition metal Mo can accept electrons from the N2σ bonding orbital, while the occupied d orbital feeds electrons back to the antibonding orbital of N2, thereby weakening the nitrogen-nitrogen triple bond, effectively adsorbing and activating N2, and significantly improving the ammonia yield.
[0024] (4) Due to the strong coupling between the transition metal Mo 4d orbital and the H1s orbital, the competitive reaction HER activity is strong and the ENRR selectivity is poor. The present invention significantly improves the ENRR selectivity by introducing a p-zone metal (Pb) that inhibits the hydrogen evolution reaction. The catalyst can be applied to electrochemical synthesis of ammonia, can effectively catalyze the nitrogen reduction reaction, and inhibit the hydrogen evolution side reaction, significantly improving the ammonia yield and Faraday efficiency of electrochemical synthesis of ammonia. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The following is further explained in conjunction with the accompanying drawings, in which carbon-coated molybdenum nitride nanoparticles embedded in lead-nitrogen co-doped carbon catalyst is represented as Mo2N@C / PbNC, carbon-coated molybdenum nitride nanoparticles embedded in nitrogen-doped carbon catalyst is represented as Mo2N@C / NC, and lead-nitrogen co-doped carbon catalyst is represented as PbNC.
[0026] Figure 1 is a scanning electron microscope (SEM) photograph of Example 1;
[0027] Figure 2 is a transmission electron microscope (TEM) photograph of Example 1;
[0028] Figure 3 is a photograph of the linear sweep voltammetry (LSV) curve of Example 1 under argon and nitrogen;
[0029] Figure 4 1 is the ammonia nitrogen concentration curve of the electrolyte before and after electrolysis in Example 1. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and beneficial effects of the present invention more clear, the present invention is described with the following specific embodiments, but the present invention is by no means limited to these examples.
[0031] Embodiment 1:
[0032] Dissolve 1.488g Zn(NO3)2·6H2O (5mmol) in 50mL methanol (solution A), dissolve 1.642g 2-methylimidazole (20mmol) in 50mL methanol solution (solution B), pour solution A into solution B, mix well and place in a 50℃ oven for 6h. Add 0.1059g Pb(NO3)2 and 0.0219g MoCl5 to the white suspension, stir for 12h, then collect the precipitate by suction filtration, wash with ethanol 2-3 times, dry in a 60℃ drying oven overnight, grind the product into a fine powder, and name it Pb / Mo / Zn-ZIF-8. Load the powder into a small porcelain boat, pass argon into a tubular furnace, and heat at a rate of 5℃min -1 , heated to 900℃ and kept at this temperature for 2h, then cooled to room temperature with the furnace to obtain black powder. The black powder was then dispersed in 1M HNO3 solution, stirred at room temperature for 4h, filtered, washed, and dried to obtain carbon-coated molybdenum nitride nanoparticles embedded in lead-nitrogen co-doped carbon catalyst.
[0033] The catalyst of Example 1 was subjected to a three-electrode test in an H-type electrolytic cell. In the three-electrode test (the electrolyte was 0.1 M sodium sulfate), the counter electrode was a graphite rod, the reference electrode was an Ag / AgCl electrode, and the working electrode was a carbon paper loaded with the catalyst. The size of the carbon paper was 1*1 cm, and the total amount of catalyst loaded on the electrode was 0.1 mg cm -2 After electrolysis at -0.1 V (vs. RHE) for two hours, the ammonia yield of the catalyst was 38.71 μg h -1 mg -1 The Faradaic efficiency is 6.6%.
[0034] Physicochemical characterization of carbon-coated MoN nanoparticles embedded in lead-nitrogen co-doped carbon catalyst. Figure 1 This is a scanning electron microscope image of the carbon-coated molybdenum nitride nanoparticles embedded in the lead-nitrogen co-doped carbon catalyst prepared in Example 1. Figure 1 It can be seen that the catalyst retains the dodecahedral morphology of the precursor ZIF-8. Figure 2 This is a transmission electron micrograph of the carbon-coated molybdenum nitride nanoparticles embedded in the lead-nitrogen co-doped carbon catalyst prepared in Example 1. It can be seen that the carbon-coated molybdenum nitride nanoparticles are stably embedded in the lead-nitrogen co-doped carbon, and the average particle size of the carbon-coated molybdenum nitride nanoparticles is 3 to 7 nm. Figure 3The electrochemical performance of the carbon-coated molybdenum nitride nanoparticles embedded in the lead-nitrogen co-doped carbon catalyst prepared in Example 1 shows the difference in the LSV curves tested under argon and nitrogen, indicating that the catalyst has ENRR performance. Figure 4 The ammonia nitrogen concentration curve of the catalyst prepared in Example 1 after electrolysis in 0.1M sodium sulfate for 2 hours is significantly higher than the ammonia nitrogen concentration curve of the blank electrolyte.
[0035] Example 2
[0036] The operating conditions were the same as those in Example 1, except that only lead salt was added. The lead-nitrogen co-doped carbon catalyst prepared in Example 2 had a conductivity of only 25.68 μg h-1 at a potential of -0.1 V (vs. RHE) in a 0.1 M sodium sulfate electrolyte. -1 mg -1 The ammonia yield and Faradaic efficiency of 3.3% were achieved. In comparison, the yield and efficiency of the carbon-coated MoN nanoparticles embedded in the lead-nitrogen co-doped carbon catalyst were increased by 1.5 times and 2 times, respectively.
[0037] Example 3
[0038] The operating conditions were the same as those in Example 1, except that only molybdenum salt was added. The carbon-coated molybdenum nitride nanoparticles embedded in the nitrogen-doped carbon catalyst prepared in Example 3 had a catalyst activity of only 24.04 μg h-1 at a potential of -0.1 V (vs. RHE) in a 0.1 M sodium sulfate electrolyte. -1 mg -1 The ammonia yield and Faradaic efficiency of 1.6% were achieved. In comparison, the yield and efficiency of the carbon-coated MoN nanoparticles embedded in the lead-nitrogen co-doped carbon catalyst were increased by 1.6 times and 4.1 times, respectively.
[0039] Example 4
[0040] The operating conditions were the same as those in Example 1, except that the molar ratio of molybdenum salt to lead salt was 4:1. The carbon-coated molybdenum nitride nanoparticles embedded with lead-nitrogen co-doped carbon catalyst prepared in Example 4 had a carbon conductivity of only 24.63 μg h-1 at a potential of -0.1 V (vs. RHE) in 0.1 M sodium sulfate electrolyte. -1 mg -1 The ammonia yield and Faradaic efficiency of 1.87% were achieved. In comparison, the yield and efficiency of the carbon-coated MoN nanoparticles embedded in the lead-nitrogen co-doped carbon catalyst were increased by 1.57 times and 3.5 times, respectively.
[0041] Example 5
[0042] The operating conditions were the same as those in Example 1, except that the molar ratio of molybdenum salt to lead salt was 1:1. The carbon-coated molybdenum nitride nanoparticles embedded with lead-nitrogen co-doped carbon catalyst prepared in Example 5 had a carbon conductivity of only 16.1 μg h-1 at a potential of −0.1 V (vs. RHE) in a 0.1 M sodium sulfate electrolyte. -1 mg -1 The ammonia yield and Faradaic efficiency of 5.1% were achieved. In comparison, the yield and efficiency of the carbon-coated MoN nanoparticles embedded in the lead-nitrogen co-doped carbon catalyst were increased by 2.4 times and 1.3 times, respectively.
[0043] Example 6
[0044] The operating conditions were the same as those in Example 1, except that the high-temperature pyrolysis temperature was 700 °C. The carbon-coated molybdenum nitride nanoparticles prepared in Example 5 embedded with the lead-nitrogen co-doped carbon catalyst had a catalyst activity of only 23.3 μg h-1 in 0.1 M sodium sulfate electrolyte at a potential of −0.1 V (vs. RHE). -1 mg -1 The ammonia yield and Faradaic efficiency of 2.2% were achieved. In comparison, the yield and efficiency of the carbon-coated MoN nanoparticles embedded in the lead-nitrogen co-doped carbon catalyst were increased by 1.65 times and 3 times, respectively.
[0045] Finally, it should be noted that the above is an exemplary description of the present invention. Obviously, the implementation of the present invention is not limited to the above-mentioned method. Any equivalent implementation scheme or changes that do not deviate from the method concept and technical solution of the present invention, such as the combination, division or repetition of features, or the direct application of the concept and technical solution of the present invention to other occasions without improvement, are all within the protection scope of the present invention.
Claims
1. A carbon-coated molybdenum nitride nanoparticle embedded with lead-nitrogen co-doped carbon catalyst, characterized in that: The catalyst presents a dodecahedral morphology with a diameter of about 137-180 nm, wherein molybdenum nitride nanoparticles are dispersed on the surface of doped carbon, the Mo content is 0.8-2.5 wt.%, and the Pb content is 0.1-0.7 wt.%.
2. The carbon-coated molybdenum nitride nanoparticle embedded lead-nitrogen co-doped carbon catalyst according to claim 1, characterized in that: The carbon-coated molybdenum nitride nanoparticles are molybdenum nitride coated with a graphite carbon layer, wherein the average particle size of the carbon-coated molybdenum nitride nanoparticles is 3-7 nm, and the thickness of the graphite carbon layer is 1-4 nm.
3. The method for preparing a carbon-coated molybdenum nitride nanoparticle embedded with a lead-nitrogen co-doped carbon catalyst according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) Dissolving zinc nitrate hexahydrate and 2-methylimidazole in anhydrous methanol by stirring; (2) pouring a methanol solution containing zinc nitrate hexahydrate into a methanol solution containing 2-methylimidazole, and keeping the temperature for a period of time to obtain a zeolite imidazolate metal organic framework material; (3) adding a certain mass ratio of transition metal molybdenum salt and p-block metal lead salt to the solution of (2) above, stirring at room temperature, and then filtering, washing, and drying the solution to obtain a zeolite imidazolate metal organic framework material adsorbing molybdenum salt and lead salt; (4) subjecting the precursor obtained in (3) to high temperature pyrolysis to obtain a black powder; (5) The black powder obtained in the above (4) is dispersed in an acid solution, stirred at room temperature, filtered, washed, and dried to obtain a carbon-coated molybdenum nitride nanoparticle embedded with a lead-nitrogen co-doped carbon catalyst.
4. The preparation method according to claim 3, characterized in that: In step (2), the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:4, and the mixture is kept in an oven at 40-70° C. for 6-8 hours.
5. The preparation method according to claim 3, characterized in that: In step (3), the transition metal molybdenum salt is one or more of molybdenum chloride, sodium molybdate, and ammonium molybdate, the p-block metal lead salt is one or more of lead chloride, lead nitrate, and lead acetylacetonate, and the molar ratio of the transition metal molybdenum salt to the p-block metal lead salt is 1:4; stirring is carried out at room temperature for 10-12 hours.
6. The preparation method according to claim 3, characterized in that: In step (4), the high temperature pyrolysis is carried out under an inert atmosphere, the holding temperature is 800-1000°C, the holding time is 2-3h, and the heating rate is 3-8°C min -1 ; The inert atmosphere is nitrogen or argon.
7. The preparation method according to claim 3, characterized in that: In step (5), the acid solution is one or more of nitric acid and acetic acid, and the concentration is 0.5-2M; stirring is carried out at room temperature for 4-6 hours.
8. Use of the carbon-coated molybdenum nitride nanoparticles embedded in lead-nitrogen co-doped carbon catalyst according to claim 1 or 2, or the carbon-coated molybdenum nitride nanoparticles embedded in lead-nitrogen co-doped carbon catalyst prepared by the preparation method of any one of claims 3 to 8 in the electrochemical synthesis of ammonia.